Socioeconomic and environmental implications of hydraulic fracturing in Mexico (International Journal of Scientific Research and Management (IJSRM), 2018)
Over the last years, hydraulic fracturing has been implemented in several countries. It is important to understand the consequences that soil and water modification has over the ecosystems and socioeconomic activity. Fracking in particular has proven to contribute to the increasing environmental and socioeconomic problems, which include climate change, losses in agricultural activity and even health risks. The number of boreholes in places like Mexico has increased, creating negative consequences for the environment and for the communities where these boreholes are located.